Supply risk propagation in international trade networks of the tungsten industry chain - Xinxin Zheng; Huajiao Li; Xiaojie Liu; Xingxing Wang; Yuqi Zhang; Qianyong Tang; Bo Ren (Humanities & Social Sciences Communications)
Abstract Tungsten plays an irreplaceable role in industrial development and high technology and is vital for national security and economic development. Supply and demand imbalances, and geopolitical and social health events, among other factors, lead to supply risks for tungsten resources in different economies. The existing studies have focused on modeling supply risk in the upstream mineral trade and lack a quantitative analysis of supply risk propagation in tungsten product trade networks from an industry chain perspective. Therefore, this paper uses trade data from 2009 to 2020 to construct an international trade network for tungsten products and applies a cascading failure model to simulate the risk propagation process in the trade network of the industry chain. The results show that China, Germany, and the US have the greatest impact ranges. The influence of economies is related to the trade export value, number of trade partners, and location. The influence of economies on the trade of midstream and downstream products is significantly related to intermediary capacity, the level of economic development, and trade closeness, with technological factors becoming increasingly important as the chain extends downward. Supply risk in upstream and midstream products is propagated mainly through indirect routes, whereas risk in downstream products is propagated mainly through direct trade relationships. The number of affected economies increases substantially when there is a small decline in the export value of tungsten products from core economies. The results can provide reference and decision support for different economies to secure the supply security and sustainability of tungsten resources.